Answer:
4p squared - 28pqStep-by-step explanation:
4p(p−7q)
=(4p)(p+−7q)
=(4p)(p)+(4p)(−7q)
=4p squared −28pq
Joey and Nolan are each solving the equation 13x - 42 = 18 - 7x. Joey's first step was to rewrite the equation as 20x - 42 = 18 while Nolan's first step was to rewrite the equation as 13x = 60 - 7x. Who is correctly applying the addition property of equality in the first step of his work? A. Only Joey B. Only Nolan C. Both Joey and Nolan D. Neither Joey nor Nolan
Answer:
Correct option: C.
(Both Joey and Nolan)
Step-by-step explanation:
The step Joey did is:
Add 7x to both sides of the equation
Then, he got:
13x - 42 + 7x = 18 - 7x + 7x
20x - 42 = 18
The step Nolan did is:
Add 42 to both sides of the equation
Then, he got:
13x - 42 + 42 = 18 - 7x + 42
13x = 60 - 7x
So both of them used correctly the addition property of equality in the first step of their work.
Correct option: C.